Cranberry capsules to prevent nosocomial urinary tract bacteriuria after pelvic surgery: a randomised controlled trial. (10th February 2017) - Letouzey, V; Ulrich, D; Demattei, C; Alonso, S; Huberlant, S; Lavigne, J‐P; de Tayrac, R
Abstract : Objective: To evaluate whether cranberries are able to prevent postoperative urinary bacteriuria in patients undergoing pelvic surgery and receiving transurethral catheterisation. Design: Randomised, double‐blind, placebo‐controlled trial. Settings: French tertiary Care centre, University Hospital. Population: A total of 272 women undergoing pelvic surgery aged 18 or older. Methods: Participants undergoing pelvic surgery were randomised to 36 mg cranberry (proanthocyanidins, PAC) or placebo once daily for 10 days. Statistical analysis was performed by a chi‐square test. Main outcome measures: The primary and secondary outcomes were postoperative bacteriuria, defined by a positive urine culture, within the first 15 and 40 days, respectively. Results: Two hundred and fifty‐five participants received the intended treatment: 132 (51.8%) received PAC and 123 (48.2%) received placebo. There were no significant differences in baseline demographics, intra‐operative characteristics or duration and type of catheterisation between the two groups. PAC prophylaxis did not reduce the risk of bacteriuria treatment within 15 days of surgery [27% bacteriuria with PAC compared with 25% bacteriuria with placebo: relative risk 1.05, 95% CI 0.78–1.4, P  = 0.763). The same result was observed on day 40. Bacteriuria occurred more often in older women with increased length of catheterisation. Conclusion: Immediate postoperative prophylaxis with PAC does not reduce the risk of postoperative bacteriuria in patients receiving short‐term transurethral catheterisation after pelvic surgery. Tweetable abstract: PAC prophylaxis does not reduce the risk of postoperative bacteriuria in patients undergoing pelvic surgery. Tweetable abstract: PAC prophylaxis does not reduce the risk of postoperative bacteriuria in patients undergoing pelvic surgery.